Certified reference materials for radionuclides in Bikini Atoll sediment (IAEA-410) and Pacific Ocean sediment (IAEA-412). (March 2016) - Pham, M.K.; van Beek, P.; Carvalho, F.P.; Chamizo, E.; Degering, D.; Engeler, C.; Gascó, C.; Gurriaran, R.; Hanley, O.; Harms, A.V.; Herrmann, J.; Hult, M.; et al.
Abstract: The preparation and characterization of certified reference materials (CRMs) for radionuclide content in sediments collected offshore of Bikini Atoll (IAEA-410) and in the open northwest Pacific Ocean (IAEA-412) are described and the results of the certification process are presented. The certified radionuclides include: 40 K, 210 Pb ( 210 Po), 226 Ra, 228 Ra, 228 Th, 232 Th, 234 U, 238 U, 239 Pu, 239+240 Pu and 241 Am for IAEA-410 and 40 K, 137 Cs, 210 Pb ( 210 Po), 226 Ra, 228 Ra, 228 Th, 232 Th, 235 U, 238 U, 239 Pu, 240 Pu and 239+240 Pu for IAEA-412. The CRMs can be used for quality assurance and quality control purposes in the analysis of radionuclides in sediments, for development and validation of analytical methods and for staff training. Highlights: Two new reference materials for radionuclides in marine sediments characterized. Massic activities of natural and anthropogenic radionuclides were certified. Aimed at QA/QC analysis and method validation for radionuclides in marine sediments.